Two New Features for AGU's Thriving Earth Exchange. Issue 45 (11th November 2014) - Udu‐gama, Natasha; Pandya, Raj
<x xml:space="preserve">Abstract</x> We are pleased to announce two new features to AGU's Thriving Earth Exchange (TEX): crowd funding and structured discussion.